Stress distribution in cylindrical and conical implants under rotational micromovement with different boundary conditions and bone properties: 3-D FEA. Issue 8 (11th June 2017) - dos Santos, Mateus Bertolini Fernandes; Meloto, Gabriel de Oliveira; Bacchi, Ataís; Correr-Sobrinho, Lourenço
Abstract: Factors related to micromovements at bone-implant interface have been studied because they are considered adverse to osseointegration. Simplifications are commonly observed in these FEA evaluations. The aim of this study was to clarify the influence of FEA parameters (boundary conditions and bone properties) on the stress distribution in peri-implant bone tissue when micromovements are simulated in implants with different geometries. Three-dimensional models of an anterior section of the jaw with cylindrical or conical titanium implants (4.1 mm in width and 11 mm in length) were created. Micromovement (50, 150, or 250 μm) was applied to the implant. The FEA parameters studied were linear vs. non-linear analyses, isotropic vs. orthogonal anisotropic bone, friction coefficient (0.3) vs. frictionless bone-implant contact. Data from von Mises, shear, maximum, and minimum principal stresses in the peri-implant bone tissue were compared. Linear analyses presented a relevant increase of the stress values, regardless of the bone properties. Frictionless contact reduced the stress values in non-linear analysis. Isotropic bone presented lower stress than orthogonal anisotropic. Conical implants behave better, in regard to compressive stresses (minimum principal), than cylindrical ones, except for nonlinear analyses when micromovement of 150 and 250 μm were simulated. The stress values raised as the micromovement amplitude increased. Non-linear analysis, presence of frictional contact and orthogonal anisotropic bone, evaluated through maximum and minimum principal stress should be used as FEA parameters for implant-micromovement studies.